Markmålsbekämpningens effekt på strategin - Bengtsson,Marcus (2020)
The purpose of this paper is to compare the outcome between naval gunfire support and strategic effect during the Falklands War. By conducting a qualitative case study regarding the effects of naval gunfire support and its effect on a unit combat effectiveness, using Ben Shalits Sequential Adjustment Model, the study will attempt to find out how a military unit is affected by stress and demoralization. Naval gunfire support was more psychological effective when employed on troops that was not sufficiently trained and suffered morale problems. Using Tony Ingessons, The Politics of Combat this result will be tested regarding the individual soldier's impact on strategic effect. Based on the observed results the findings were tested against a causal chain process of hypothesis and reliability. The conclusion of this study is that the influence of naval gunfire support, on the individual soldier had a strategic effect. The demoralizing effect of naval gunfire support was a vital part of the outcome of the war.
Keywords: Falklandskriget; Markmålsbekämpning; Naval Gunfire Support; Stridsvärde